2019
DOI: 10.1002/ange.201902476
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Prodrugs by NIR‐Triggered Release of Exogenous Enzymes for Locoregional Chemo‐photothermal Therapy

Abstract: Enzymes have been used to direct the conversion of prodrugs in cancer therapy. However, non‐specific distribution of endogenous enzymes seriously hinders their bioapplications. Herein, we developed a near‐infrared‐triggered locoregional chemo‐photothermal therapy based on the exogenous enzyme delivery and remolded tumor mivroenvironment. The catalytic efficiency of enzymes was enhanced by the hyperthermia, and the therapeutic efficacy of photothermal therapy (PTT) was improved owing to the inhibition of heat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Very recent treatment combinations with PTT include photodynamic therapy, chemotherapy, and immunotherapy, and a lot of papers reported the outstanding effect via such synergized modality. 87,[189][190][191][192] However, reviews on the combination strategies can be readily found, and for ease of elaboration, we are going to be more involved in discussing the future of PTT alone in the following.…”
Section: Photothermal Therapy (Ptt)mentioning
confidence: 99%
“…Very recent treatment combinations with PTT include photodynamic therapy, chemotherapy, and immunotherapy, and a lot of papers reported the outstanding effect via such synergized modality. 87,[189][190][191][192] However, reviews on the combination strategies can be readily found, and for ease of elaboration, we are going to be more involved in discussing the future of PTT alone in the following.…”
Section: Photothermal Therapy (Ptt)mentioning
confidence: 99%
“…The GNs have been approved by the US Food and Drug Administration, and the liposomes have completed Phase III clinical trial. The nanocomplexes were further utilized to encapsulate exogenous enzymes (denoted as MYR@HGNs), and nontoxic prodrug glucoraphenin could be activated into therapeutic sulforaphene by the exogenous enzyme (Figure 6b; Cheng et al, 2019). The cumulative enzymes released from the prepared MYR@HGNs were rapidly up to 50.1% within 3 min upon irradiation, and more than 70% after 5 min (Figure 6c).…”
Section: Chemo-photothermal Therapymentioning
confidence: 99%
“…(c) Release profiles of the exogenous enzyme from MYR@HGNs with or without 808 nm laser irradiation (2 W cm −2 , 3 min). (d) Western blotting analysis of different protein expressions in 4T1 cells after different treatments (Reprinted with permission from Cheng et al (2019), Copyright 2019 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim). (e) Schematic representation of NIR light‐triggered photodynamic therapy and chemo‐cascade therapy.…”
Section: Applications Of Nir‐initiated Prodrugmentioning
confidence: 99%
“…Despite encouraging results, tumor recurrence and metastasis during PTT remain challenging; insufficient heat within tumors, the upregulation of heat shock proteins in tumor cells, and inflammatory responses can lead to incomplete tumor cell death and promote resistance and metastasis. [9][10][11][12][13] In addition, in vivo PTT of tumors is usually achieved by raising the tumor temperature >50°C, which may damage the skin and surrounding normal tissues. 14,15 PDT that relies on tumor-localizing photosensitizers to generate singlet oxygen ( 1 O 2 ) and other reactive oxygen species to kill tumor cells upon light excitation represents a supplementary phototherapy to PTT.…”
Section: Introductionmentioning
confidence: 99%